History of education as a scientific discipline and a teaching subject in Montenegro – past, present and perspectives. - Zorić, Vučina (Paedagogica Historica, 2022)
This paper studies the beginnings, development, transformations, challenges and perspectives of History of Education (in orig. Istorija pedagogije) as a scientific discipline and a teaching subject in Montenegro. For this purpose, the paper analyses the appearance, status and representation of History of Education as a teaching subject over a 130-year period, as well as the significant role it has had in the development of educational workers in Montenegro. Although generally considered a fundamental educational discipline, the History of Education has lost its importance as a teaching subject, especially when it comes to its low representation in the education of future primary-school teachers and subject teachers in primary and secondary schools or its reduction to a semester course in the Study Programme for Science of Education (in orig. Studijski program za pedagogiju). On the other hand, the History of Education has never lost significance as a scientific educational discipline in Montenegro, i.e. its content has always aroused interest. Beside the numerous dilemmas and challenges the History of Education faces, this work considers a number of recent studies which can significantly influence its status and development perspectives as well as the status of Science of Education (in orig. Pedagogija) in Montenegro.